PERCEPTIONS OF SERVICE-ORIENTATION AND TRUST OF TAX OFFICERS BETWEEN MILLENIALS, X, AND BABY BOOMERS - Elisa Tjondro; Kezia Gabriel Santosa; Nathasa Prayitno (MIX: JURNAL ILMIAH MANAJEMEN, 2019)
The purpose of this study is to examine differences in perceptions of generations related to service-orientation and trust to tax officers. Changes traditional paradigm of the relationship between tax officers and taxpayers from “cops and robbers” to "clients" cause the research in perception of service-orientation and trust to tax officers to be necessary in order to improve voluntary tax compliance. This study also explains perceptions of tax fairness in three perspectives which are vertical equity, horizontal equity, exchange equity. The survey was conducted in 2018 with 165 self-employment individual taxpayers consisting of three generations, Millennials, X, and Baby Boomers from two types of work, retail/production and services business. This study uses quota sampling to collect respondents and use ANOVA statistical tests. The results of the study indicate differences in perceptions regarding service-orientation between generations. However, there are no differences in perception related trust to tax officers between generations. This research also found that Millenials, X, and Baby Boomer have different perceptions of vertical equity, horizontal equity, and exchange equity